The Joint Committee, drone strikes and self-defence: Caught in no man's land? - White, Nigel D. (Taylor & Francis, 2016)
The Joint Committee’s Report centres around a crucial issue concerning the use of drones by the UK to target suspected terrorists outside of armed conflict, namely the meaning and application of the right of self-defence, and whether such strikes meet the key elements of such a right – that there is an imminent armed attack necessitating the use of lethal force against a terrorist or terrorists. The Report is clear in its finding that ‘it is the Government’s policy to be willing to use lethal force, outside of armed conflict …, against individuals suspected of planning an imminent terrorist attack against the UK, as a last resort, when there is no other way of preventing the attack’. This brief op-ed explores the Joint Committee’s interrogation of this policy under both the law governing the use of force by states (the jus ad bellum), and the law applying when a state uses lethal force outside of armed conflict (international human rights law), arguing that self-defence is the thread that links both. Although the Report does consider both legal frameworks, and makes some very telling criticisms of the government’s policy, it does not fully explore the relationship between the two, and so is caught in no man’s land between them. It is concluded that it is only by understanding that self-defence arguments operates at two levels that we can properly assess any government claim that a particular drone strike is justifiable as a lawful use of force.